NILAI-NILAI PENDIDIKAN KARAKTER DALAM TRADISI TAJINAN (SORA DAN SAPPAR) MASYARAKAT KECAMATAN KRAKSAAN, KABUPATEN PROBOLINGGO - Shinta Fauziyah; Wahyu Djoko Sulistyo (Al-Fikru : Jurnal Pendidikan Dan Sains, 2021)
Indonesia, with its characteristic diversity, has many races, cultures, languages, traditions that are spread all over the islands in Indonesia. has various kinds of diversity with noble values that are still maintained to this day. However, it is undeniable that in the era of modernization and globalization itself, the younger generation who should be the inheritors of the culture, tradition, language, that is in their area are slowly being left behind. Therefore, it is very important to instill local values or traditions, traditional culture, regional languages in students, so that they do not lose their identity as Indonesian people which are rich in diversity. In the Probolinggo area itself, there are many local traditions that are not widely known by students, but there are also traditions that are already known but they do not know the origin, meaning or philosophy of the existing traditions. One of the traditions that almost all students know, especially in the Kraksaan sub-district is the tajinan "Tajin sora and Sappar", but unfortunately they do not know the origin or meaning of the tajinan itself and there are also character values contained in this tajinan tradition. Kata kunci: Character Matter, Tajinan, Sora dan Sappar